Kehidupan Sosial Masyarakat Arab Masa Awal Kehadiran Pendidikan Islam - Satir, Muhammad (Al-Fikr: Jurnal Pendidikan Islam, 2019)
The social condition of the Arabs before Islam was known as the 'period of ignorance' or the age of ignorance, caused by social, political, morality and social relations in real conditions of error. To understand the jahiliyyah habits of the Arabs, the all-wise God sent an Apostle, Muhammad SAW. polite, humble, generous, brave, honest and trustworthy, they believe in "al-amiin". Arab education at the beginning of Islamic education was not well organized. However, education developed and they had at that time divided into three fields of knowledge. First, the knowledge of the nasab (history), history, and the influence of religion. Second, Ru'ya (dream) knowledge. Third, knowledge about reflection, the knowledge which according to Imam Gazali is a despicable science. While the science of poetry is the knowledge that is only controlled by people who are approved, and it is a sign of anxiety from the Arab community at that time.